Relationships of DTI findings with neurocognitive dysfunction in children with Type 1 diabetes mellitus - TOPRAK, HÜSEYİN; Toprak, Huseyin; ALKAN, ALPAY; Yetis, Huseyin; KURTCAN, SERPİL; Alkan, Alpay; ARALAŞMAK, AYŞE; Filiz, Mekiya; CESUR, YAŞAR; Kurtcan, Serpil; Aralasmak, Ayse; Aksu, Mehmet S.; et al. (My University, 2016)
Objective: To determine whether there were diffusion tensor imaging (DTI) changes in the brain among children with Type 1 diabetes mellitus (DM) and investigate the correlation between the fractional anisotropy (FA) and apparent diffusion coefficient (ADC) values and neurocognitive functions.
Keywords: Diabetes mellitus